2011
DOI: 10.1111/j.1469-8749.2011.03918.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of the pediatric patient with hypotonia: perspective from a hypotonia specialty clinic and review of the literature

Abstract: CPT Carnitine palmitoyltransferase MDC1ACongenital muscular dystrophy type 1A SLO Smith-Lemli-Opitz syndrome SMA Spinal muscular atrophy AIM Hypotonia is a symptom of diminished tone of skeletal muscle associated with decreased resistance of muscles to passive stretching, which can be caused by abnormalities of the central nervous system, any element of the lower motoneuron, or both. Hypotonia is not a specific diagnosis, but can be part of over 500 different genetic disorders, with many other conditions waiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 0 publications
0
43
0
5
Order By: Relevance
“…Overall differential diagnosis of CMD has to take into account congenital myopathies, ie, myopathies with typical structural or ultrastructural features on the muscle biopsy, congenital myotonic dystrophy, congenital myasthenic syndromes, early-onset metabolic myopathies, Marinesco–Sjögren syndrome, and other subtypes of congenital ataxia, congenital disorders of the motor neuron and the peripheral nerve, and other genetic syndromes such as Prader–Willi syndrome, 7 and the more frequently acquired conditions leading to profound hypotonia, such as acute hypoxic ischemic encephalopathy and neonatal sepsis.…”
Section: Common Clinical Aspects Of Cmdmentioning
confidence: 99%
“…Overall differential diagnosis of CMD has to take into account congenital myopathies, ie, myopathies with typical structural or ultrastructural features on the muscle biopsy, congenital myotonic dystrophy, congenital myasthenic syndromes, early-onset metabolic myopathies, Marinesco–Sjögren syndrome, and other subtypes of congenital ataxia, congenital disorders of the motor neuron and the peripheral nerve, and other genetic syndromes such as Prader–Willi syndrome, 7 and the more frequently acquired conditions leading to profound hypotonia, such as acute hypoxic ischemic encephalopathy and neonatal sepsis.…”
Section: Common Clinical Aspects Of Cmdmentioning
confidence: 99%
“…However, a CGH was performed because the phenotype was evocative of genomic imbalance [Miller et al, 2010] and chromosome microarray analysis has been proposed as a valuable tool for genetic evaluation of pediatric patients with hypotonia [Lisi and Cohn, 2011].…”
Section: To the Editormentioning
confidence: 99%
“…Hypotonia is a state of low muscle tone accompanied by a slower response speed together with reduced muscle strength [3][4]. Cowley et al [5] reported that the force generated by the knee extensor muscle of DS individuals is approximately 40%-70% less than that generated by individuals with intellectual disabilities other than DS and those with normal intellectual ability.…”
Section: Introductionmentioning
confidence: 99%